2005
DOI: 10.1093/aob/mci234
|View full text |Cite
|
Sign up to set email alerts
|

The Perisperm-endosperm Envelope in Cucumis: Structure, Proton Diffusion and Cell Wall Hydrolysing Activity

Abstract: The lipid layer seems to contribute to the semi-permeability of the PE envelope. The diffusion of protons might create an acidic environment conducive to the activity of cell wall hydrolases, namely endo-beta-mannanase (EC 3.2.1.78) and beta-glucanase [beta(1-->3)glucanohydrolase; EC 3.2.1.6], which, in turn, may play a role in the weakening of the PE envelope necessary for the protrusion of the radicle in cucumber and muskmelon seeds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…The endosperm of the castor seed prevents the penetration of fluorescent dye, indicating the presence of an endosperm semi-permeable layer [17]. In muskmelon [19] and cucumber [18], the semi-permeable layer was present in the perisperm-endosperm envelope. But in Sudan grass [13], the semi-permeable layer was located at the inner aleurone layer, connected to the undifferentiated cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The endosperm of the castor seed prevents the penetration of fluorescent dye, indicating the presence of an endosperm semi-permeable layer [17]. In muskmelon [19] and cucumber [18], the semi-permeable layer was present in the perisperm-endosperm envelope. But in Sudan grass [13], the semi-permeable layer was located at the inner aleurone layer, connected to the undifferentiated cells.…”
Section: Discussionmentioning
confidence: 99%
“…The result was different from other species. Yim and Bradford [19] had reported that in muskmelon seed, the semi-permeable layer formed at 40 dpa, whereas in cucumber seeds [18], this layer formed at 45 dpa. In Sudan grass, the semi-permeable layer emerged at 16 dpa [25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations